Shifts in monetary policy and exchange rate dynamics: is Dornbusch's overshooting hypothesis intact, after all? - Rüth, Sebastian (Discussion paper series, 2019)
How do nominal exchange rates adjust after surprise contractions in monetary policy? While the seminal contribution by Dornbusch provides concise predictions - exchange rates appreciate, i.e., overshoot on impact before depreciating gradually - empirical support for his hypothesis is at best mixed. I argue that the failure to discover overshooting may result from assumptions researchers have imposed to recover structural VARs. Specifically, simultaneous feedback effects between interest rates and exchange rates, which are inherently forward-looking variables, are often excluded or modeled alongside with strong restrictions. In this paper, I identify U.S. monetary policy shocks using surprises in Federal funds futures around policy announcements as external instruments, which recent literature has established to represent the appropriate laboratory in settings encompassing macroeconomic and financial variables. Resulting adjustments of the dollar, conditional on shifts in policy, generally align with Dornbusch's predictions during the post-Bretton-Woods era, including Volcker's tenure as Fed Chair.